Design of Intercative Game to Train Children’s Skills Based on Microcontroller - Diyajeng Luluk Karlina (International Journal of Mechanical, Electrical and Civil Engineering, 2026)
This research aims to design and develop a simple Dino-themed game based on a microcontroller, with the display using an I2C LCD. The game is inspired by the offline Dino game on Google Chrome, adapted to run on an Arduino Uno microcontroller. The research method used is Research and Development (R&D), consisting of stages such as needs analysis, system design, simulation using Wokwi, hardware assembly, programming, and testing. The system uses push buttons as input and a 16x2 I2C LCD as the output display. The testing results show that the system can respond quickly to user input and display character movement and score updates dynamically on the LCD screen. Although the graphical capability of the LCD is limited, the game runs well and successfully demonstrates the basic concepts of microcontroller programming as well as interactive input-output processing. Further development is recommended to enhance the graphical interface and add features such as sound effects and progressive difficulty levels.